Interações taxonômicas entre parasitos e morcegos de alguns municípios do estado de Minas Gerais - Érica Munhoz de Mello (2017)
Bats are hosts of a high number of endo and ectoparasites, however, parasitism in these animals is still little investigated. The objective of this work was to identify morphologically the species of helminths and ectoparasites, to evaluate molecularly the presence of hemoparasites and to molecularly identify some species of helminthes of bats of the State of Minas Gerais. Three hundred nineteen bats received by the Zoonoses Control Center of the municipality of Belo Horizonte from January 2013 to March 2016, were necropsied, being: 208 Molossidae, 66 Phyllostomidae, 43 Vespertilionidae and 2 Emballonuridae. Of the total number of animals, 65 (20.38%) presented helminths. The most frequently parasitized host was Eumops glaucinus. The parasitism in females (60%) was higher than in males (40%) and 100% of parasitized hosts were adults. Three hundred forty one specimens of parasites were recovered: 94 Rictulariidae, 4 Spiruridae, 41 Onchocercidae, 19 Molineidae, 55 Capillariidae (Nematoda), 20 Lecithodendriidae, 49 Anenterotrematidae, 50 Urotrematidae (Trematoda) and 17 Hymenolepididae (Cestoda), in addition to four larvae of nematodes unidentified and 11 specimens of unidentified trematodes. The parasitism by more than one helminth species was verified in 21 hosts. The most prevalent helminth was Pterygodermatites (Paucipectines) sp. Of the total of 2093 specimens of bats examined for ectoparasites, only 94 (4.49%) had parasites, and a total of 260 specimens were recovered: 28 Spinturnicidae, 122 Macronyssidae, 12 Trombiculidae (Acari, Mesostigmata), an Argasidae (Acari, Ixodida), 4 Polyctenidae (Insecta, Hemiptera), one Pulicidae (Insecta, Siphonaptera), 91 Streblidae (Insecta, Diptera) and one unidentified insect specimen. The municipality with the highest number of parasitized hosts was Belo Horizonte. Bats were most frequently parasitized by streblid batflies and macronissids mites, with 51 and 25 infected hosts, respectively. Among the flies, Paratrichobius longicrus was the most prevalent species, found in 73.54% (37/51) of hosts parasitized by Streblidae family specimens. Among mite and tick families, the macronissídeo Chiroptonyssus venezolanus was the most prevalent species found in 44% (11/25) of the hosts parasitized by the Acari subclass. Female bats showed more ectoparasites (68.6%) than males (31.4%), and parasitism was higher in adults (87.2%) than in newborn animals (7.7%) and young individuals (5.1%). Parasitism by more than one species of ectoparasite was verified in 10 hosts. With regard to hemoparasites, preliminary results showed 13 bats positive for Trypanosomatidae and 47 for Piroplasmida, two samples being positive for both. Among the sequenced samples of the Piroplasmida, 3 samples were identified with Babesia sp. and 15 as Theileria sp. Their sequencing showed a high similarity to Babesia bigemina and to Theileria orientalis/Theileria buffeli, respectively. This work contributes to an epidemiological survey of parasite species of bats with abnormal behavior in the state of Minas Gerais.